Chapter 4 Welfarist Psychiatry Goes Global - McConnell, Doug (Elsevier/Academic Press, 2020)
We begin by describing welfarist psychiatry before outlining the relevant challenges to improving global mental health and explaining how welfarist psychiatry meets those challenges.